Failure assessment of cracked uni-planar square hollow section T-, Y- and K-joints using the new BS 7910:2013+A1:2015 - Kolios, Athanasios (2019)
This paper covers the validation of standard safety assessment procedure in the new BS 7910:2013+A1:2015 for cracked uni-planar square hollow section (SHS) T-, Y- and K-joints using the finite element analyses. The procedure is based on the failure assessment diagram (FAD) method. A completely new and robust finite element mesh generator is developed, and it is validated using the full-scale experimental test results. FAD curves are constructed using the elastic J-integral ( Je ), the elastic-plastic J-integral ( Jep ) and the plastic collapse load ( Pc ) values calculated using the 3D cracked models of the joints. The results reveal that the standard Option 1 FAD curve of the new BS code is not always safe in assessing the safety and integrity of cracked uni-planar SHS joints. Therefore, a penalty factor of 1.2 for plastic collapse load is recommended to move all the constructed Option 3 FAD curves above the standard Option 1 curve. The new Option 3 FAD curves are found to generate optimal solutions for cracked uni-planar SHS T-, Y- and K-joints.